2007
DOI: 10.1007/s10533-007-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

Pools and fluxes of carbon in three Norway spruce ecosystems along a climatic gradient in Sweden

Abstract: This paper presents an integrated analysis of organic carbon (C) pools in soils and vegetation, within-ecosystem fluxes and net ecosystem exchange (NEE) in three 40-year old Norway spruce stands along a north-south climatic gradient in Sweden, measured 2001Sweden, measured -2004. A process-orientated ecosystem model (CoupModel), previously parameterised on a regional dataset, was used for the analysis. Pools of soil organic carbon (SOC) and tree growth rates were highest at the southernmost site (1.6 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 56 publications
5
51
1
Order By: Relevance
“…In addition root litter and field layer litter should be accounted for. Figures on these fluxes lack in the present investigation , but based on results from Sweden, the figures on root litter are in the same order of magnitude as the above ground litterfall (Kleja et al 2008). This means that the present difference in litter fall C input to the soil could be some 1.9 Mg C ha -1 a -1 (65%) higher in the even-aged system.…”
Section: Litter Fall and Soil Co 2 Effluxsupporting
confidence: 56%
See 2 more Smart Citations
“…In addition root litter and field layer litter should be accounted for. Figures on these fluxes lack in the present investigation , but based on results from Sweden, the figures on root litter are in the same order of magnitude as the above ground litterfall (Kleja et al 2008). This means that the present difference in litter fall C input to the soil could be some 1.9 Mg C ha -1 a -1 (65%) higher in the even-aged system.…”
Section: Litter Fall and Soil Co 2 Effluxsupporting
confidence: 56%
“…In the present investigation the C storage in the vegetation (above ground parts) is some 0.3-0.6% of the C in the trees (Table 2). However, the annual ground vegetation turnover rate is high and it has been demonstrated that C input to soil from field layer can account for more than 25% of total ecosystem production (Kleja et al 2008) in a 40 year old Picea abies stand. …”
Section: Tree Yield and C Sequestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Mäkipää et al (1999) demonstrates for example how uptake of N and decomposition were coupled with an empirical multiplier that was related to annual values of transpiration as the forcing conditions for the decomposition of soil organic material. In recent work, Svensson et al (2007) applied the CoupModel (Jansson and Karlberg 2004) with a daily time step for estimating decomposition rates and N supply in order to evaluate effects of climate and N on ecosystem productivity in Sweden. They concluded that it was not possible to explain the tree growth rate in northern Sweden with the conventional decomposition mineralization model.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations were made for well-drained soils in 4 selected regions in Sweden, representing differences in the current climate and N deposition rates, using the CoupModel, previously parameterized on a regional-based dataset (Svensson et al 2007). Specific objectives were to: (i) Identify how a change in climate affected abiotic factors of importance for ecosystem C dynamics; (ii) analyze how a change in climate affected the rate of processes governing the accumulation of carbon in vegetation and litter production, compared to the rate of processes regulating the rate of SOC decomposition; and (iii) identify the extent to which limiting factors for key ecosystem processes are expected to change, for instance the role of moisture and nitrogen.…”
Section: Introductionmentioning
confidence: 99%